The Unstoppable Spread of English in the Global University - Salomone, Rosemary (International Higher Education, 2022)
As English has spread across higher education worldwide, it has generated ongoing debate and a wealth of scholarship raising academic and national concerns, but with little, if any, pause or retreat on policies and practices. This article examines that puzzling disconnect within the broader framework of the rise of English as the dominant lingua franca, its historical grounding, its social and economic implications, and its diverse course within Europe and postcolonial countries.